Promoter and enhancer elements in the rearranged alpha chain gene of the human T cell receptor. - Luria, S (1987)
We cloned and compared the sequence of a rearranged human T cell receptor (TCR) V alpha J alpha gene and its germline counterparts. The only difference in the coding region sequence was confined to the joining region where three nucleotides, TTG, unaccountable by either V alpha or J alpha sequence, were present. By nuclease S1 mapping we identified the mRNA start of the alpha chain 70 nucleotides upstream from the initiator ATG. A 600 bp fragment containing the sequences upstream to the ATG drives the expression of the bacterial chloramphenicol acetyltransferase (CAT) gene. This promoter activity is T cell specific since it can be demonstrated in human T cells but not in B cells or HeLa cells. A 1.1 kb BamHI- HindIII fragment located 5' to the first exon of the C alpha gene was found to enhance transcription from either the heterologous SV40 promoter or the homologous TCR alpha chain promoter. This enhancement activity was independent of the location of the fragment with respect to CAT and was specific to lymphoid cells (either T or B cells) but cannot be demonstrated in HeLa cells.